Toward a Holistic and Integrative Pedagogy: Furthering the Conversation - Coulter, Dale; Yong, Amos 1965- (2024)
We wish to express our thanks to our interlocutors and to the editors of Pneuma for facilitating this exchange as part of an issue on higher education within Pentecostalism. It is a humbling experience to have our work digested by seasoned administrators long at work in pentecostal higher educational spheres who share with us the calling and task of forging a Christ-formed and Spirit-infused life of the mind. Maybe the best way to hand off our dialogue is simply to reiterate Mark Cartledge’s point, in his lead essay in this issue of the journal, of the attempt to capture in the phrase “head, heart, and hands” a holistic and transformational approach to personal and spiritual formation. Come Holy Spirit, inspire our collaborative conversation and educational efforts.
Keywords: Pedagogy; Higher Education; Pentecostal; Holy Spirit